Reproduction as Work: Addressing a Gap in Current Economic Rights Discourses - Lauren Danielowski (Harvard FXB Center for Health and Human Rights, 2023)
In 2022, the global commercial surrogacy industry was valued at approximately US$14 billion. This paper explores the issue of surrogacy to reveal how international human rights standards and labor laws treat reproduction as work, building on previous scholarship analyzing similar framing at the grassroots level in Mexico. I argue that the failure to recognize surrogacy as labor is rooted in three lacunae: (1) contemporary policies and practices around surrogacy globally pay little attention to the well-being and rights fulfillment of surrogates themselves, particularly the economic rights of surrogates; (2) the stigma of surrogacy as sexualized care work results in neglect of the labor rights of surrogates in mainstream economic rights discourses; and (3) relevant international rights law has not yet addressed the economic rights of surrogates, nor has it effectively articulated the interdependent relationship between economic rights and reproductive rights. Lastly, I discuss where reproductive rights and economic rights overlap in existing human rights conventions and standards and what possibilities these offer for articulating the interdependence of reproductive and economic rights and for advancing the labor rights of surrogates.